(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
This study presents a comprehensive analysis of phenolic compounds and water-soluble vitamins in an ethanolic extract obtained from a 1:1 mixture of poplar (Populus alba) and willow (Salix) using high-performance liquid chromatography (HPLC). The qualitative and quantitative determination of gallic acid, salicylic acid, rutin, quercetin, apigenin, as well as vitamins C, B1, B2, B3, B6, B9, and PP was performed.